RELATIONSHIP BETWEEN THE LEVEL OF EDUCATION DEVELOPMENT OF WOMEN WITH CHILDREN (AGES 3-5 YEARS) IN KADIPATEN BOJONEGORO - HIDAYAH, WAQIDIL; LUTHFIA, ERIEN; Kariima, Adini Cipta (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2015)
ABSTRACTEducation on early childhood development is a process of changing personalities, attitudes and understanding of development that is appropriate for toddlers. The lack of knowledge becomes a major factor in the failure in the process of early childhood development, for example, mothers who have little education then it will be difficult to digest the message delivered to educate a child in a foster child. The aim of this study was to analyze the relationship between maternal education level with the development of children 3-5 years old.This research is a correlation cross sectional approach. Population is the mother and toddlers 3-5 years as many as 42. Both of these variables was tested significance of using data analysis cross table with a value of ?: ? value of 0.05 obtained: 0,000 <? 0,05 so Ho rejected, which means there Relationship Education Level Mother With Toddler Development (Th 3-5.It is concluded that there is a relationship of education level of respondents with the development of toddlers 3-5 Tahun.Respondent continued attitude they have to educate early childhood development and give each other information, or exchange experience with other respondents so as to increase knowledge better. Keywords: education, early childhood development